BIOLOGICAL ROLE OF AMINO ACIDS IN THE HUMAN BODY: METABOLIC, REGULATORY, AND CLINICAL PERSPECTIVES - Farkhod Kholbayevich Rakhmonov; Temurjon Shokhdavlatovich Ulmasov (Modern American Journals, 2026)
Amino acids are commonly introduced as the structural units of proteins, but contemporary biochemistry places them at the center of metabolic integration and clinical interpretation. Beyond protein synthesis, amino acids supply carbon skeletons for energy metabolism, mediate nitrogen transfer through transamination and deamination reactions, and serve as precursors for multiple low-molecular regulators including neurotransmitters, nucleotides, nitric oxide, and antioxidants. The maintenance of amino acid homeostasis depends on coordinated digestion and absorption, inter-organ trafficking, de novo synthesis of nonessential amino acids, and regulated catabolism in liver, muscle, intestine, and kidney. Because these processes intersect with signaling networks that control growth, autophagy, immunity, and stress adaptation, disturbances of amino acid metabolism are involved in inherited enzymopathies, liver failure, chronic kidney disease, diabetes, and cancer. This narrative review summarizes key metabolic routes and clinically relevant laboratory indicators that support diagnostics and targeted nutritional or pharmacological interventions, with a brief nutritional perspective on high-quality protein sources rich in essential amino acids.
Keywords: Amino acids; nitrogen metabolism; transamination; urea cycle; mTOR signaling; glutathione; clinical biochemistry; nutritional proteins.